Accuracy of neurosonography and MRI in clinical management of fetuses referred with central nervous system abnormalities. (August 2014) - Paladini, D.; Quarantelli, M.; Sglavo, G.; Pastore, G.; Cavallaro, A.; D'Armiento, M. R.; Salvatore, M.; Nappi, C.
ABSTRACT Objective To assess the accuracy of expert neurosonography (two‐ and three‐dimensional NSG) in the characterization of major fetal central nervous system (CNS) anomalies seen at a tertiary referral center and to report the differential clinical usefulness of magnetic resonance imaging (MRI) used as a second‐line diagnostic procedure in the same cohort. Methods This was a retrospective analysis of all 773 fetuses with confirmed CNS abnormalities referred to our center between 2005 and 2012. The following variables were analyzed: gestational age at NSG and MRI, NSG and MRI diagnoses, indication for MRI (confirmation of NSG findings; diagnostic doubt; search for possible additional brain anomalies), association with other malformations, diagnostic accuracy of NSG vs MRI (no additional clinical value for either MRI or NSG; additional information with clinical/prognostic significance on MRI relative to NSG; additional information with clinical/prognostic significance on NSG relative to MRI, NSG and MRI concordant but incorrect) and final diagnosis, which was made at autopsy or postnatal MRI/surgery. Results CNS malformations were associated with other anomalies in 372/773 (48.1%) cases and were isolated in the remaining 401 (51.9%) cases. NSG alone was able to establish the diagnosis in 647/773 (83.7%) cases. MRI was performed in 126 (16.3%) cases. The indication for MRI was: confirmation of NSG diagnosis in 59 (46.8%) cases; diagnostic query (in the case of inconclusive or uncertain finding on NSG) in 20 (15.9%) cases; search for possible additional brain anomalies in 47 (37.3%) cases. NSG and MRI were concordant and correct in 109/126 (86.5%) cases. Clinically relevant findings were evident on MRI alone in 10/126 (7.9%) cases (1.3% of the whole population) and on NSG alone in 6/126 (4.8%) cases; in all six of these cases, MRI had been performed at < 24 weeks of gestation. In one case, both NSG and MRI diagnoses were incorrect. The main type of malformation in which MRI played an important diagnostic role was space‐occupying lesions, MRI identifying clinically relevant findings in 42.9% (3/7) of these cases. Conclusions (1) In a tertiary referral center with good NSG expertise in the assessment of fetal CNS malformations, MRI is likely to be of help in a limited proportion of cases; (2) MRI is more useful after 24 weeks of gestation; (3) the lesions whose diagnosis is most likely to benefit from MRI are gross space‐occupying lesions. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd